PENGARUH KOMPETENSI PEGAWAI TERHADAP KINERJA TENAGA KEPENDIDIKAN PADA POLITEKNIK â€œXâ€ DI PEKANBARU - Yapentra, Arhipen; Risman, Risman; Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2022)
ABSTRACT : This study entitled The Effect of Competence on the Performance of Education Personnel at Polytechnic "X" Pekanbaru. The population and sample of this study were all 79 civil servants of the Educational Personnel at Polytechnic "X" Pekanbaru. The research method used is descriptive and quantitative methods and then analyzed by simple linear regression method. The results of the recapitulation of the average value of the competency variable are 4.11, meaning that the respondents' answers to all statements of Competence for Education Personnel are in the GOOD category. Based on the results of the t test, it was found that the value of t_count > t_table (9,714 > 1,991) and a significance < 0.05 (0.000 < 0.05). This means that competence has a positive and significant effect on the Performance of Civil Servants of Education Personnel at the Polytechnic "X" Pekanbaru. The R square value of 0.551 or 55.1% means that competence has an influence on the Performance of Civil Servants of Education Personnel at the Polytechnic "X" Pekanbaru by 55.1% and the rest (44.9%) is influenced by other variables not examined in this study. this research